Market Opportunity Analysis of Fermentative Floating Feed Products Non-Extrusion of High Protein Empirical Study in Bogor District, West Java Province - Udin Ahidin (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
The purpose of this study is to find out the market opportunities and marketing strategies of High Protein Non-Extrusion Floating Feed-in Bogor Regency, West Java Province. Research method with descriptive approach. The population in this study were all freshwater fish farmers in Bogor Regency, West Java Province, and samples used in this study were freshwater fish farmers, especially catfish in Bogor Regency, West Java Province. Data collection methods: observation, interview, and documentation study. Data analysis method with descriptive statistics. The results showed that the market opportunities for High ProteinNon-Extrusion Floating Feed products in Bogor Regency, West Java Province were very high, dominated by the Catfish culture market by 82.397%, the remaining 11.165% by Ornamental Fish cultivators, and 6.438% by Gurame Fish cultivators. For the marketing strategy carried out, especially the distribution strategy (place) and promotion strategy (promotion), the product strategy (product) and price strategy (price) have their own advantages and uniqueness compared to other catfish feed competitors.